2021
DOI: 10.21037/jgo-20-426
|View full text |Cite
|
Sign up to set email alerts
|

Favorable tumor biology in locally advanced pancreatic cancer—beyond CA19-9

Abstract: Patients with pancreatic ductal adenocarcinoma (PDAC) are frequently staged as unresectable locally advanced pancreatic cancer (LAPC) at the time of diagnosis. Recently, the administration of multi-agent induction chemotherapy has resulted in treatment response in up to 60% of these patients rendering their tumors technically resectable. Operative strategies have evolved to allow for successful oncologic resection of LAPC. These technically complex procedures involving vascular resections and reconstructions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…Future studies should search for additional biomarkers reflecting tumor behavior, such as circulating tumor DNA, to further improve staging. 21,22 Moreover, a decrease in standardized uptake value of PDAC on positron emission tomography scans after neoadjuvant treatment is a promising prognostic factor, especially in patients who are nonsecretors of CA 19-9. [23][24][25][26] Several smaller studies found that a poor performance status of ≥2 was a poor prognostic factor for OS for patients with PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should search for additional biomarkers reflecting tumor behavior, such as circulating tumor DNA, to further improve staging. 21,22 Moreover, a decrease in standardized uptake value of PDAC on positron emission tomography scans after neoadjuvant treatment is a promising prognostic factor, especially in patients who are nonsecretors of CA 19-9. [23][24][25][26] Several smaller studies found that a poor performance status of ≥2 was a poor prognostic factor for OS for patients with PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…13 Several alternative serum biomarkers are recently described, such as carcinoma embryonic antigen (CEA), 45 DUPAN-2, 46 and circulating tumor cells/DNA. 47 Besides serological tumor markers, FDG-PET combined with either CT or magnetic resonance imaging may be a valuable tool to assess the biological disease response during/after chemo (radio) therapy, especially in patients with non-elevated CA19-9. 48 This is underlined by the 2021 Japanese Society of Hepato-Biliary-Pancreatic Surgery guideline, which proposed the implementation of the metabolic tumor activity on fluorodeoxyglucose positron emission tomography as biological parameter in the A-B-C resectability criteria from Isaji and colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…Second, there remains a proportion of patients with non-elevated baseline CA19-9, and patients without CA19-9 due to a Lewis antigen negative phenotype for whom other indicators for tumor biology should be used 13 . Several alternative serum biomarkers are recently described, such as carcinoma embryonic antigen (CEA), 45 DUPAN-2, 46 and circulating tumor cells/DNA 47 . Besides serological tumor markers, FDG-PET combined with either CT or magnetic resonance imaging may be a valuable tool to assess the biological disease response during/after chemo (radio) therapy, especially in patients with non-elevated CA19-9 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Tumor biology shows signi cant impact on the prognosis of patients with malignancy and has been incorporated into the staging system to improve the accuracy of prognostic prediction [10,11] . Since both tumor burden and malignant degree could re ect the characteristics of tumor biology [12,13] , we supposed that combination of the factors which represent tumor burden and malignant degree would provide a full understanding of tumor biology on prognosis of cancer, and incorporating factors associated with tumor biology into staging system could improve the accuracy of the TNM staging system in predicting prognosis. Carbohydrate antigen 19 − 9 (CA19-9) is associated with the tumor burden 14] and histology grade is associated with the degree of malignancy [15,16] .…”
Section: Introductionmentioning
confidence: 99%